6(v-9)=-2v-14

Simple and best practice solution for 6(v-9)=-2v-14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(v-9)=-2v-14 equation:


Simplifying
6(v + -9) = -2v + -14

Reorder the terms:
6(-9 + v) = -2v + -14
(-9 * 6 + v * 6) = -2v + -14
(-54 + 6v) = -2v + -14

Reorder the terms:
-54 + 6v = -14 + -2v

Solving
-54 + 6v = -14 + -2v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '2v' to each side of the equation.
-54 + 6v + 2v = -14 + -2v + 2v

Combine like terms: 6v + 2v = 8v
-54 + 8v = -14 + -2v + 2v

Combine like terms: -2v + 2v = 0
-54 + 8v = -14 + 0
-54 + 8v = -14

Add '54' to each side of the equation.
-54 + 54 + 8v = -14 + 54

Combine like terms: -54 + 54 = 0
0 + 8v = -14 + 54
8v = -14 + 54

Combine like terms: -14 + 54 = 40
8v = 40

Divide each side by '8'.
v = 5

Simplifying
v = 5

See similar equations:

| 9(3n-3)=(4n+8)+2 | | 0.3x+3=-2.3x+0.4 | | 7(x-1)+3(3-x)=5(1-x)-3(2x+1) | | 2(90-x)-6=124 | | 961=400+2x | | 15+5(x-10)=3(x-1) | | 16x+16=16x-16 | | 13t-52+8t=21t+28-10 | | 5(z+1)=z+8 | | 5+-6= | | 180=y+5x+20 | | 12x+4=1(x+12) | | -8x-12=36 | | -11+-9= | | 5x+2(x+7)=6x+14 | | -8z-18=-10 | | 11/27=4/9-2x/3 | | 12x+4x^2+9=0 | | -6+18= | | (2x-3)(x+8)=(x-6)(x+4) | | 5t-12=2t+3 | | 1/5(10a-15)=3-2a | | 5x+20=7x-20 | | 125-7x=11x+25 | | 3x^2-41=-4x^2-7x-24 | | 8+6z-5=9z+4-2z | | 9x-8x+3=11 | | 14=12x-2x | | 10x^2-27xy+11y^2=0 | | -8y-6y=9+5 | | 2y+4=9y-3 | | 85+-0.5y+y=180 |

Equations solver categories